2023
DOI: 10.3389/frfst.2023.1168896
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance in Italian poultry meat production chain: a one-health perspective comparing antibiotic free and conventional systems from the farming to the slaughterhouse

Abstract: In this study a multidisciplinary approach was applied in order to determine the diffusion of resistant bacteria and selected antibiotic resistance genes in antibiotic-free and conventional broiler farms. Litter samples coming from the two farming types and surface sponges obtained from carcasses at slaughterhouse level were screened by end-point PCR targeting specific resistance for tetracycline, ampicillin, sulfonamide, aminoglycoside, carbapenem, nitrofurantoin, vancomycin, quinupristin-dalfopristin, lincom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Based on an antibiotic susceptibility test, amoxicillin, tetracyclines, or aminoglycosides were applied up to 5 days via drinking water. The environmental sampling procedure allowed us to collect samples representative of the entire area, recovering litter pools at various points in the shed, namely, at the center and four corners [ 16 , 40 ]. Each flock was sampled twice, i.e., at 7 (T0) and at 35–45 days (T1) (near to slaughtering).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on an antibiotic susceptibility test, amoxicillin, tetracyclines, or aminoglycosides were applied up to 5 days via drinking water. The environmental sampling procedure allowed us to collect samples representative of the entire area, recovering litter pools at various points in the shed, namely, at the center and four corners [ 16 , 40 ]. Each flock was sampled twice, i.e., at 7 (T0) and at 35–45 days (T1) (near to slaughtering).…”
Section: Methodsmentioning
confidence: 99%
“…Despite this, the real efficacy of antibiotic-free farming in reducing the dissemination of resistant bacteria and ARGs is not completely understood. Published data demonstrated that some differences are evident, comparing intestinal microbial composition and ARGs abundance at the farm level; however, often, this evidence does not persist with respect to the carcasses at slaughterhouses or meat retailers, with particular regard to food-borne pathogens [ 12 , 13 , 14 , 15 , 16 ]. Therefore, continuous monitoring of the AMR profiles in poultry farming should be encouraged in order to highlight any changes or to identify additional sources of resistant microorganism dangerous for humans and animals.…”
Section: Introductionmentioning
confidence: 99%